A Case of Angioimmunoblastic T-cell Lymphoma was Diagnosed Initially as Kimura’s Disease and Castleman Disease (Journal of Medicine, 2025)
Kimura disease (KD) is a rare chronic inflammatory disorder, and Castleman disease is a rare lymphoproliferative syndrome. Castleman disease (CD) is associated with an increased risk for lymphoma. The patient described here is a 52-year-old female who came with one-year history of fever, generalized lymphadenopathy and polyserositis. The patient was initially diagnosed on 2 occasions respectively as Kimura’s disease and then as Castleman disease. Eventually, she had a confirmed diagnosis of Angioimmunoblastic T-cell lymphoma, after which she received 2 cycles of combination chemotherapy and her condition improved. She received a total of 6 cycles of chemotherapy over the next 6 months, but unfortunately, she passed away after receiving the 6th cycle.J MEDICINE 2025; 26: 63-66